A butterfly effect in cancer. (2nd January 2016) - Vogt, Peter K; Hart, Jonathan R; Yates, John R
Abstract : A point mutation in PIK3CA, the gene encoding the α isoform of class I phosphatidylinositol 3-kinase, induces extensive remodeling of the transcriptome and proteome, resulting in a gene signature that specifically resembles that of the basal subtype, but not other types, of breast cancer.